ئامادەكردنی پێوەرێك بۆ هەڵسەنگاندنی لێهاتوویی نواندن لای فێرخوازانی قۆناغی شەشەمی بنەڕەتی - حسین, پ.د.جواد نعمت; یوسف, ی.ت. سارا جلال جمال (Sulaimani Journal for Humanities, 2023)
The aim of this study was to prepare a scale to assess acting skills among sixth grade students. In this study, the descriptive method was used to conduct it because it is appropriate to the nature of the subject and the objective of the study For this purpose, the researcher prepared a special scale that consisted of (12) items, according to scientific procedures, the apparent honesty of the scale was determined by obtaining the opinion of experts in the subject and its stability A sample consisting of 28 sixth grade students, 16 boys and 12 girls, was repeated two weeks later. After statistically treating the data using the Person equation, it was found that the stability value of the scale is (0.92) which is high and reliable It constitutes the results of the study and as the study ended with some recommendations.